2021
DOI: 10.3390/su13115969
|View full text |Cite
|
Sign up to set email alerts
|

Durability Performance Evaluation of Rubberized Geopolymer Concrete

Abstract: Unfortunately, the production of cement impacts pessimistically on environments since it emits CO2—a principal Green House Gas (GHG)—encouraging the earth-heating dilemma. Moreover, it necessitates not only high temperature produced by the devouring of narrow natural mineral coal resources to obtain very high amounts of energy, but it also gulps down natural limestone deposits as a raw material that is found confined in nature to obtain intense energy. Quite recently, geopolymerisation—an exothermic process, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The pores in geopolymer are filled with alumino-silcates, which lower its permeability. There are more pores persisting in the OPC concrete to enable the hydration of the cement [ 44 ]. Due to low permeability, a lower amount of acid will penetrate into the structure to erode the interior.…”
Section: Resultsmentioning
confidence: 99%
“…The pores in geopolymer are filled with alumino-silcates, which lower its permeability. There are more pores persisting in the OPC concrete to enable the hydration of the cement [ 44 ]. Due to low permeability, a lower amount of acid will penetrate into the structure to erode the interior.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that several studies have shown that geopolymer can be a possible alternative adsorbent to the existing commercial absorbent, there are certain limitations that need to be addressed further. The first source of concern is a scarcity of raw resources [ 264 , 265 , 266 , 267 ]. A number of aluminosilicate materials and industrial wastes can be utilized to make geopolymers [ 268 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Geopolymers are a class of inorganic materials in the form of geopolymer paste, geopolymer mortar, geopolymer concretes, etc., for the construction and infrastructure industry produced through the process of geopolymerization-the alkaline activation of solid alumina-silicate precursors, either as industrial by-products or materials of geological origin at low temperature in alkaline medium [40,41]. Geopoly-meric materials can bring the significant environmental and economic advantages owing to the opening for the incorporation of diverse profuse waste streams sans compromising durability, strength, and the sustainability attributes to an optimum level along with low carbon footprint [41][42][43][44][45][46][47][48][49][50][51][52][53]. The workability, mix design, mechanical characteristics, durability, and micro-structure, etc., of geopolymer composites have recently been studied by researchers [41][42][43][54][55][56][57][58][59].…”
Section: Geopolymeric Materialsmentioning
confidence: 99%